Analysis and evaluation of tools supporting group work in the cloud - Gustaw, Paweł; Miłosz, Elżbieta (Journal of Computer Sciences Institute, 2019)
The aim of this work was to analyze and evaluate the tools used for group work in the cloud and based on the adopted criteria, choose the best tool. The choice of programs was targeted at users such as students and small business employees. The work uses literature analysis and research methods. The work consists of chapters in which attention is focused on the use of cloud computing, explanation of models and types of clouds, general presentation of selected tools, presentation of the analysis of the problem and research methods, and presentation of research and conclusions resulting from them.